Iron Deficiency Anemia is Associated with Hearing Loss in the Adult Population - Schieffer, Kathleen M. (JAMA Otolaryngol Head Neck Surg, 2017)
IMPORTANCE: Hearing loss in the US adult population is linked to hospitalization, poorer self-reported health, hypertension, diabetes, and tobacco use. As iron deficiency anemia (IDA) is a common and easily correctable condition, further understanding the association between IDA and all types of hearing loss in a population of United States adults may help open new possibilities for early identification and appropriate treatment. OBJECTIVE: To evaluate the association between sensorineural hearing loss (SNHL) and conductive hearing loss (CHL) and IDA in adults aged 21–90 years in the United States. DESIGN: The prevalence of IDA and hearing loss (ICD-9 codes 389.1 (SNHL), 389.0 (conductive hearing loss), and 389 (combined hearing loss)) were identified in this retrospective cohort study. IDA was determined by low hemoglobin and ferritin levels for age and sex. Associations between hearing loss and IDA were evaluated using Chi squared test. Logistic regression modeled the risk of hearing loss among those with IDA. SETTING: Penn State Health Milton S. Hershey Medical Center, Hershey, PA. PARTICIPANTS: Adults 21–90 years of age. MAIN OUTCOME MEASURES: Hearing loss RESULTS: Out of 305,339 patients in the study population, there was a 1.6% (n=4,807) prevalence of hearing loss and 0.8% (n=2,274) prevalence of IDA. Both SNHL and presence of combined hearing loss was significantly associated with IDA. Logistic regression confirmed increased odds of SNHL (adjusted OR 1.82 [95% CI 1.18–2.66]) and combined hearing loss (adjusted OR 2.41 [95% CI 1.90–3.01]) among adults with IDA, after adjusting for sex. CONCLUSIONS AND RELEVANCE: IDA was associated with SNHL and combined hearing loss in a population of adult patients. Further research is needed to better understand the potential links between IDA and hearing loss, and whether screening and treatment of IDA in adults could have clinical implications in patients with hearing loss.